Use of sesame seed cake as replacement for fishmeal in diets for catfish, Clarias gariepinus (Burchell 1822) (1998)
A 6-week feeding trail was conducted in glass tanks with juvenile Clarias gariepinus to examine the effects of partial and total replacement of fishmeal with sesame seed cake protein. Five semi-purified isonutrogenous diets (I,II, III, IV, V containing 40% protein) and isocaloric (3.9 Kcal gross energy/g of dry diet) were formulated to contain varying percentage of 0%, 25%, 50%, 75% and 100% solvent extracted sesame seed cake in replacement for fishmeal. Diet 1 (0% sesame seed cake protein) was the control. Specific growth rate (SGR), food conversion ratio (FCR) and protein efficiency ratio (PER) were not significantly different (P>0.05) from diets I,II,III,IV in weight gain, SGR, FCR and PER. The results of this study suggest that sesame seed cake cannot to totally replace fishmeal in diets for Clarias gariepinus. However, at 25% replacement of fishmeal by sesame seed cake will give similar SGR, FCR, and PER when compared to an all fishmeal diet, but was found to be richer in methionine and arginine.